PROTECTING LIFE BELOW WATER: LESSONS LEARNED FROM JAKARTA AND BALI - Lusita Astuti Nusantari; Rudi Sukandar; Muhamad Rizal Ibrahim (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
As the Millennium Development Goals (MDGs) ended, the United Nations followed them up with 17 Sustainable Development Goals (SDGs). One of the goals, Life Below Water, is very strategic to Indonesia given its position as the biggest maritime archipelagic nation in the world. However, Indonesia’s life below water faces threats as pollutants from human activities end up in the sea. Using Structural Human Ecology (SHE) theory, this article discusses the issue using cases in Jakarta and Bali and how the two provinces have dealt with the problem. Employing the qualitative method through document analyses, this study found that the two provinces have used different approaches in solving the problem. While Jakarta has its law regarding the issue, Bali has more progressive law in curbing the disposal of waste, especially plastic, to the river leading to the sea. Law enforcement and education have become the keys to ensuring that industrial and domestic actors to stop irresponsible disposal of waste.